DIFFERENCES BETWEEN EMPLOYED AND UNEMPLOYED PEOPLE IN SATISFACTION WITH LIFE, SUBJECTIVE HAPPINESS, AND LATENT AND MANIFEST BENEFITS OF WORKDIFFERENCES BETWEEN EMPLOYED AND UNEMPLOYED PEOPLE IN SATISFACTION WITH LIFE, SUBJECTIVE HAPPINESS, AND LATENT AND MANIFEST BENEFITS OF WORK - Strizović, Ivana; Mratinković, Aleksandar (Primenjena psihologija, 2017)
The problem of this study was to explore differences in well-being between employed and unemployed persons in Serbia, as well as the differences between the employed and the unemployed in prediction of well-being based on manifest and latent benefits of employment. The study consisted of 237 participants from Serbia, whereby 61.6% were employed. Participants varied by gender, work status, education, place of living and socioeconomic status, but employed and unemployed participants did not differ according to socio-demographic variables. The used instruments were Satisfaction With Life Scale, Subjective Happiness Scale, and The Latent and Manifest Benefits Scale, which measured benefits of employment. Results showed that the employed people had higher satisfaction with life, more financial security, and more structured time than the unemployed. However, there was no difference in subjective happiness between the employed and unemployed participants. Using hierarchical regression analysis it was shown that the best predictor of satisfaction with life in the subsample of the employed was financial status, followed by more social contacts and better time structure and social status. The best predictor of satisfaction with life in the subsample of unemployed was latent benefit which included social contacts, and then financial status. Based on these results we could assume that, in Serbia, financial strain is more important than latent benefits in prediction of satisfaction with life, at least in the case of employed people.